Biosensor for measuring the anti-diabetic potential of medicinal plants - Md. Mohiuddin
Three alternative electro-enzyme techniques were developed for measuring antidiabetic potential of medicinal plants. All three techniques are based on the inhibition of α- glucosidase (AG) enzyme in the conversion of para-nitrophenyl-α-D-glucopyranoside (PNPG) into para-nitrophenol (p-NP) which is catalyzed by AG enzyme. The first technique, multi-walled carbon nanotubes (MWCNTs) paste electrode comprised of a uniform mixture of MWCNTs powder and mineral oil at the ratio of 60: 40 and used with free enzyme and PNPG solution. The second technique, screen printed carbon nanotubes (SP-CNTs) electrode was based on commercial screen printed electrode (SPE) and used with free enzyme and PNPG solution. The third technique, disposable biosensor, was based on the extension of the first and second electrodes where AG enzyme was covalently immobilized onto amine functionalized multi-walled carbon nanotubes (MWCNTs-NH2) followed by entrapment of PNPG as a substrate using freezing–thawing treated poly(vinyl alcohol) on the SP-CNTs. The PNPG was entrapped at low pH to prevent the premature reaction between PNPG and immobilized enzyme. The immobilized AG enzyme and PNPG on MWCNTs-NH2 was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The applicability of each technique for measuring antidiabetic was tested using three types medicinal plants namely Tebengau (Ehretia laevis), Cemumar (Micromelum pubescens), Kedondong (Spondias dulcis) and a commercial antidiabetic drug Acarbose via spectrophotometric, cyclic voltammetry (CV) and amperometric methods. The results showed that the inhibition obtained in the presence of Tebengau plant extracts is higher than that obtained with Acarbose, Cemumar and Kedondong. The kinetic of immobilized and non-immobilized enzyme was measured using Lineweaver-Burk equation. The CV response for inhibition of AG enzyme activity within the biosensor by Tebengau plant extracts showed a linear relationship in the range from 0.5 – 3.5 mg/mL and an inhibition detection limit was 0.5 mg/mL. The biosensor exhibited good sensitivity (1.037 μA/mg Tebengau plant extracts) and rapid response within 22 seconds. The biosensor retains about 79.16 % its initial activity even after 30 days when stored at 40C. The repeatability and reproducibility of the technique and disposable biosensor was satisfactory. Therefore, the techniques and disposable biosensor could be used for measuring the anti-diabetic potential of medicinal plants as well as to monitor the activity of commercial antidiabetic drugs.